Research on the SH-CCT and PWHT of improved new type SA738 Gr. B nuclear power steel. (November 2020) - Jianlin, Zhang; Ping, Zhu; Xunuo, Yang; Gangang, Wang; Jiancang, Zhao
Abstract: The Gleeble-3180 machine is used to determine the simulated HAZ continuous cooling transformation (SH-CCT) curves of improved new type SA738 Gr. B nuclear power steel by expansion method, metallographic method and hardness method. The t8/5 time increase from 5 s to 6000 s and the influence of cooling rate on microstructure and phase transition are analyzed. The hardness changes before and after tempering treatment are compared with the samples so as to analyze the process and function of tempering. This reasearch provides theoretical and data support for improving welding technology and promoting the development of nuclear steel.